Social Adjustment as Predicted by Cultural Identity and Acculturative Stress - Deshmukh, Arjun; Sharma, Neha (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the predictive roles of cultural identity and acculturative stress on social adjustment among university students in India. Methods and Materials: A correlational descriptive research design was employed, and a total of 595 participants were selected through stratified random sampling based on the Krejcie and Morgan sample size determination table. Participants were undergraduate and postgraduate students from various universities across India. Data were collected using three standardized instruments: the Social Adjustment Scale–Self-Report (SAS-SR), the Multigroup Ethnic Identity Measure (MEIM), and the Social, Attitudinal, Familial, and Environmental Acculturative Stress Scale (SAFE). Data analysis was conducted using SPSS version 27. Descriptive statistics were computed, followed by Pearson correlation coefficients to assess relationships among variables. Multiple linear regression analysis was used to evaluate the predictive power of cultural identity and acculturative stress on social adjustment. Findings: Descriptive results showed that participants reported moderate levels of social adjustment (M = 3.24, SD = 0.51), high cultural identity (M = 3.67, SD = 0.42), and moderate acculturative stress (M = 2.41, SD = 0.48). Pearson correlation analysis revealed a significant positive relationship between cultural identity and social adjustment (r = .47, p < .01), and a significant negative relationship between acculturative stress and social adjustment (r = −.39, p < .01). Multiple regression analysis indicated that cultural identity (β = .41, p < .001) positively predicted social adjustment, while acculturative stress (β = −.33, p < .001) negatively predicted it. The model explained 31% of the variance in social adjustment (R² = .31). Conclusion: Interventions promoting cultural identity and reduce acculturative stress may support better social functioning in multicultural student populations.